Effect Of Recycled Acrylonitrile Butadiene Rubber (NBRr) On Polypropylene (PP) / (NBRr) / Banana Skin Powder (BSP) Composites - Habibah Yusof (School of Environmental Engineering, Universiti Malaysia Perlis, 2015)
The aim of the study is to produce a PP/NBRr/BSP composite and also compatibilized the PP/NBRr/BSP composite with a PPMAH. Below are the details of the objectives focused for this research. To study the effects of NBRr loadings on PP/NBRr/BSP composite. To determine the mechanical, chemical and thermal properties of PP/NBRr//BSP composite. To investigate the effect of PPMAH compatibilizer on PP/NBRr/BSP composite.